2004
DOI: 10.1182/blood-2003-04-1290
|View full text |Cite
|
Sign up to set email alerts
|

Soluble MD-2 activity in plasma from patients with severe sepsis and septic shock

Abstract: In this paper, we show that plasma from patients with severe sepsis and septic shock but not normal plasma supports lipopolysaccharide (LPS) activation of epithelial cells expressing Toll-like receptor 4 (TLR4). Recombinant soluble myeloid differentiation protein-2 (MD-2) complemented normal plasma and allowed LPS activation of epithelial cells to levels measured with "septic" plasma, whereas soluble MD-2-depleted plasma lost its effects. The same "MD-2 activity" was found in urine from a patient with septic s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
93
0

Year Published

2005
2005
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(97 citation statements)
references
References 54 publications
4
93
0
Order By: Relevance
“…It has been suggested that sMD-2 might play an important role in modulating the innate responses of epithelial cells that express TLR4 but not MD-2 (39). Relevant to this finding, a recent report has suggested that plasma-derived sMD-2 might play a major role in promoting organ inflammation during the progression of Gram-negative bacterial-induced septic shock (53). Information derived from additional investigation of msbB LPS and P. gingivalis LPS interactions with LBP, CD14, and MD-2 will be critical in further elucidating the molecular mechanism of LPS-dependent antagonism.…”
Section: Discussionmentioning
confidence: 97%
“…It has been suggested that sMD-2 might play an important role in modulating the innate responses of epithelial cells that express TLR4 but not MD-2 (39). Relevant to this finding, a recent report has suggested that plasma-derived sMD-2 might play a major role in promoting organ inflammation during the progression of Gram-negative bacterial-induced septic shock (53). Information derived from additional investigation of msbB LPS and P. gingivalis LPS interactions with LBP, CD14, and MD-2 will be critical in further elucidating the molecular mechanism of LPS-dependent antagonism.…”
Section: Discussionmentioning
confidence: 97%
“…Dulbecco's modified Eagle's medium (DMEM), nonessential amino acids, sodium pyruvate, penicillin, and streptomycin were obtained from Gibco Invitrogen (Karlsruhe, Germany), ␣-ketoglutaric acid, ␤-amino propionitrile, and fetal calf serum (FCS) were from Sigma (St. Louis, MO), and recombinant human tumor necrosis factor ␣ (rHuTNF␣) was from R&D Systems (Minneapolis, MN). The inhibitors U-0126, SB203580, MG-132, and SP600125 were from Calbiochem (San Diego, CA), IFN␥ was from Roussel Uclaf (Paris, France), the anti-human TLR-2 mAb (T2.5), the anti-human TLR-4 mAb (15C1) (36,37), and the control isotype mAb were kind gifts from Dr. G. Elson (NovImmune, Plan-les-Ouates, Switzerland). The antagonists used, lipopolysaccharide (LPS) from Rhodobacter sphaeroides (LPS-RD) and LPS from Escherichia coli, were from InvivoGen (San Diego, CA) and Difco Laboratories (Detroit, MI), respectively.…”
Section: Methodsmentioning
confidence: 99%
“…Plasma from patients with severe sepsis and septic shock and even normal plasma appears to contain soluble MD-2 that elicits LPS activation in TLR4-transfected HEK293 cells and HUVECs (16,27), whereas the patients' plasma tends to somewhat decrease, although not significantly, LPS responsiveness in leukocytes and differentiated THP-1 cells expressing both TLR4 and MD-2 on cell surface. Previous studies (6,28) have shown that soluble MD-2 interacts with the extracellular TLR4 domain and confers LPS responsiveness on TLR4-transfected cells.…”
Section: Discussionmentioning
confidence: 95%